Structural, thermal and electrical studies of a novel rubidium phosphite tellurate compound - Beyribey, Berceste; Hallinder, Jonathan (ELSEVIER SCI LTD, 2012)
Structural, thermal and electrical properties studies of rubidium phosphite tellurate, RbH(PO3H)center dot Te(OH)(6), were performed. An endothermic peak, which reached a completion at about 315 degrees C accompanied with a weight loss of 4.6 wt.%, was attributed to dehydration. Four types of pellets were produced, namely pellets A, B, C and D. Pellet A was tested with platinum carbon paper electrode, and pellets B, C and D were tested with gold electrodes. Both pellets A and B were studied from 113 degrees C to 317 degrees C for 135 h. Pellet C was first investigated from room temperature to 176 degrees C for 360 h. After cooling down to room temperature, a second measurement with pellet C was carried out under the same conditions as used for pellets A and B. Pellet D, on the other hand, was heated up to 450 degrees C, kept at that temperature for 2 h and then cooled down to room temperature prior to the conductivity measurements. It was observed that the conductivities of pellets A and B decreased to values of 5.2 x 10(-8) S cm(-1) 6.6 x 10(-7) S cm(-1) at 317 degrees C, respectively, and an unexpected rise in the conductivity (9.89 x 10(-6) S cm(-1) at 317 degrees C) was seen with pellet C. Dehydration of RbH(PO3H)center dot Te(OH)(6) might be responsible for this unexpected rise in the conductivity of pellet C. The monoprotic part RbH(PO3H) of RbH(PO3H)center dot Te(OH)(6) apparently became diprotic (Rb2H2P2O5) part of Rb2H2P2O5 center dot[Te(OH)(6)](2) after dehydration. The measured conductivity of pellet D, which was dehydrated prior to the measurement, reached a value of 5.41 x 10(-5) S cm(-1) at 317 degrees C and showed a good stability over-each-run time and temperatures measurement up to 317 degrees C. The dehydrated compound, Rb2H2P2O5 center dot[Te(OH)(6)](2), has also a higher hydrogen density relative to the starting compound, RbH(PO3H)center dot Te(OH)(6). It is deduced that completion of the dehydration can be responsible for the unexpected rise in the conductivity of RbH(PO3H)center dot Te(OH)(6). This unusual case is important for studies in solid acid proton conductors. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Solid acids; Rubidium dihydrogen phosphite tellurate; Proton conductivity; Impedance spectroscopy; Thermal analysis; MIXED SOLID-SOLUTION; SELENATE TELLURATE; DIELECTRIC-PROPERTIES; X-RAY; CONDUCTIVITY; ACID; TRANSITION; CRYSTAL; Materials Science